Experimental investigation on performance and emission of a small generator spark ignition engine fueled with hydrogen peroxide-gasoline - Zainol, Sabri Adlan (2022)
Automobiles produced various harmful substances and gaseous such as carbon monoxide (CO), unburned hydrocarbon (UBHC), nitrogen oxides (NOx), and lead. These substances contribute to air pollution. Some existing vehicles such as motorcycles, cars, light trucks, watercraft, small aircraft, and boats are consuming gasoline as burning fuel in internal combustion engines. One key issue concerning gasoline is during its burning process as the fuel will unleash those harmful substances into the air. Hence, to solve the problem, an alternative fuel is essential to fight against scarcity and global warming. One of the promising alternative fuels for internal combustion engines is hydrogen peroxide (H2O2) mixture which could be utilized in spark-ignition engines. Therefore, the objectives of this study are to analyze the effects of H2O2-gasoline fuel blends on engine performance and emission, to compare the results between H2O2-gasoline fuel blends and gasoline alone operations in terms of performance and emission of the engine, and to determine the optimum percentage of H2O2-gasoline fuel blends that gives the best performance and better emission for the engine. H2O2 is used as the working medium in H2O2 enhancement where heat is produced and H2O2 is rapidly decomposed into water (H2O) that generates oxygen and steam which can improve the internal energy. As a result, an increase in engine power output is then achieved. Spark ignition engine fueled with hydrogen peroxide blends generates a satisfactory improvement in power output and efficiency of thermal. Nevertheless, it causes the release of higher HC, NOx, and CO2 concentrations. In this study, experimental investigations were performed on the performance and emission properties of a spark ignition engine operating on hydrogen peroxide-gasoline fuel blends. The experiment was performed on a single-cylinder, 4-stroke spark-ignition engine. 5 %, 10 %, and 15 % of hydrogen peroxide-gasoline fuel blends were derived with polysaccharide emulsifiers to minimize surface tension between both gasoline and hydrogen peroxide. The obtained results are then compared with the performance and emission of the same engine that runs on gasoline only. In this work, the collected results suggest that better engine performance with 10% of hydrogen peroxide and gasoline blend is achieved. The results show that the highest indicated work, heat release rate, peak pressure, indicated thermal efficiency at all engine speeds is obtained with 10 % of hydrogen peroxide and gasoline blend. The hydrogen peroxide-gasoline fuel blends indicate higher harmful gaseous in comparison with 100% gasoline. However, a 15 % fuel blend shows the lowest value of harmful gaseous. It is concluded that a 10 % hydrogen peroxide-gasoline fuel blend is the ideal blend for power requirements and acceptable emission controls. Generally, hydrogen peroxide-gasoline fuel blends appear to be a potential approach to improve the performance and quality of emissions in a spark-ignition engine.